2021
DOI: 10.15547/ast.2021.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fattening period duration on meat productivity of domestic quails

Abstract: Abstract. The study was conducted with 224 domestic quails from the specialized meat-type WG line. The duration of fattening period and sex on productive traits, slaughter traits and meat quality of quails was evaluated. The study has shown that the longer duration of the fattening period in quails from the meat-type line WG was associated with lower production efficiency, with more reduction after the 35th day of life. The production efficiency in male quails was lower compared to that in females. The dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Also, according to Petek et al (2022) , younger quail meat samples had greater pH levels, suggesting a decrease in water-holding capacity, while older quail carcasses had higher values. In contrast, Lukanov et al (2021) found no significant differences in the pH value between the slaughter age (28, 35, and 42 d) and gender. According to Maynard et al (2023) , processing different live weights and straight-run broilers may have contributed to the higher yield of broilers in large bird markets, with quality varying between males and females at a given weight.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Also, according to Petek et al (2022) , younger quail meat samples had greater pH levels, suggesting a decrease in water-holding capacity, while older quail carcasses had higher values. In contrast, Lukanov et al (2021) found no significant differences in the pH value between the slaughter age (28, 35, and 42 d) and gender. According to Maynard et al (2023) , processing different live weights and straight-run broilers may have contributed to the higher yield of broilers in large bird markets, with quality varying between males and females at a given weight.…”
Section: Discussioncontrasting
confidence: 61%
“…Similar data might have resulted from the small difference in slaughter ages. Furthermore, Lukanov et al (2021) indicated that the color and pH levels in the breast muscle of meat-type quail (WG line) ranged from 5.75 to 6.26 and were unaffected by gender or the age when the quail was slaughtered (28, 35, and 42 d).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the centuries-old tradition of raising quail for meat and eggs, it was only in the early 20th century that quail's ability to produce eggs was discovered to be greater than that of other poultry species, and in later years interest in meat-type quail production increased again. According to Lukanov et al (2023) , currently global quail egg production is 1.2 to 1.3 million tons, while quail meat production is 200 to 240,000 tons.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, quail meat is obtained mainly by slaughtering Pharaoh quail broilers at 40 to 45 d of age at 150 to 210 g; slaughtering surplus reproductive males at 7 wk of age, and slaughtering spent quails after the egg production period ( Kraszewska, 1978 ; Rutkowski, 2005 ). Studies conducted in recent years indicate that the rearing of Japanese quail kept in the intensive system is best completed at the age of 4 to 5 wk at a body weight of 160 to 259 g ( Lukanov et al, 2021 ; Dalle Zootte and Cullere, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Black pigmentation in the birds is called Fibromelanosis. Abnormal accumulation of eumelanin in tissues causes the Fibromelanosis trait in the chickens body and its internal organ (Hutt 1949;Lukanov & Genchev 2013). The presence of a duplication rearrangement in the genomic region containing the Endhotelin3 gene (EDN3) on chromosome 20 cause of Fibromelanosis (Fm) mutation in Cemani and Silkie chickens (Shinomiya et al 2012;Dorshorst et al 2010;Dharmayanthi et al 2017).…”
Section: Introductionmentioning
confidence: 99%